Penilaian kondisi lembaga bisnis konservasi lingkungan dan ekowisata bahari berbasis GSTC di Wangi-Wangi, Kabupaten Wakatobi, Sulawesi Tenggara - Sahari, Sariamin; Nasrun; Normayasari; Ferlin, Akhmatul; Utami, Dewi; Alsita, Indah; Runtu, Kezia Gloria Apriliana; Mansyur, La Ode; Isman, Khairuddin; Musrianton, Muhammad; Admadja, Alfi Kusuma; Harudin (Universitas Halu Oleo, 2024)
The conservation enterprise growth in Wakatobi Regency, Southeast Sulawesi, which is focused on ecotourism or natural and cultural tourism, have varied greatly in recent years regarding the environmental of Wakatobi, both in terms of appearance, human resources and variety of types. Eco-tourism has developed quite well and advanced in several places, such as Bali, but there are also those that have not succeeded in making ecotourism a leading sector and priority, such as Wakatobi Regency. To improve public understanding of sustainable tourism the Global Sustainable Tourism Council (GSTC) has issued a special guideline for sustainable tourism. This research is one of the GSTC indicators in the management of several marine conservation destinations on Wangi-Wangi Island, namely WTC, DCDC, and FPW Sombu. By utilizing a qualitative descriptive approach, this research aims to expand knowledge about the WTC, DCDC, and FPW Sombu as one of the mainstay ecotourism destinations in Wakatobi Regency, determine whether the management of these destinations has fulfilled the GSTC criteria, and determines the development strategy of the ecotourism object in question using the GSTC indicators. The results show that, so far, the management of the WTC, DCDC, and the FPW Sombu almost largely does not meet the GSTC sustainable tourism indicators. The focus of the aspects studied are indicators of (A) sustainable development, (C) cultural sustainability and (D) environmental sustainability, which show that the management of the three marine ecotourism destinations has not been maximally considered. Overall, all three destinations are still weak, according to the analysis of the with the GSTC criteria. A review of the sustainable tourism aspects of the GSTC can provide information on the development of the WTC, DCDC, and the FPW Sombu, so that they meet the requirements to become sustainable marine ecotourism destinations in the GSTC. in terms of attractions, amenity, and accessibility.